Film and decorative sheet

By controlling the nanoindentation hardness difference between the surface protective layer and the transparent resin layer in a decorative sheet film, the film achieves excellent scratch, impact, and weather resistance, addressing peeling issues and enhancing long-term surface performance.

JP2025060370APending Publication Date: 2025-04-10DAI NIPPON PRINTING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024026458
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-29
Filing Date
2024-02-26
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

Decorative sheets for building materials face challenges in maintaining long-term surface performance due to peeling issues between the surface protective layer and underlying layers, despite improvements in weather resistance from added weathering agents.

Method used

A film with a surface protective layer laminated on a transparent resin layer, where the difference in nanoindentation hardness between the two layers is controlled between 200 MPa to 270 MPa, using a mixture of thermosetting and ionizing radiation curable resins, and incorporating additives such as isocyanate components, polyhydric alcohols, and acrylic polyol components.

Benefits of technology

The solution provides excellent scratch resistance, impact resistance, and weather resistance by preventing peeling between the surface protective layer and the transparent resin layer, while also enhancing the durability and performance of the decorative sheet.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060370000001_ABST
    Figure 2025060370000001_ABST
Patent Text Reader

Abstract

To provide a film excellent in scratch resistance, impact resistance and weather resistance.SOLUTION: In the film, at least a surface protective layer is laminated on a transparent resin layer. The difference in nanoindentation hardness between the surface protective layer and the transparent resin layer is 200 MPa or more and 270 MPa or less. The surface protective layer contains a thermosetting resin and / or an ionizing radiation-curable resin. The transparent resin layer contains a homopolypropylene-based resin. The nanoindentation hardness of the surface protective layer is 300 MPa or more and 400 MPa or less. The nanoindentation hardness of the transparent resin layer is 50 MPa or more and 140 MPa or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a film for use in a decorative sheet, and to a decorative sheet having said film laminated thereon. [Background technology]

[0002] Decorative sheets for building materials are required to have excellent surface performance so that they can withstand long-term use as surface decorative materials for residential interior materials, etc. For example, in order to improve weather resistance, attempts have been made to optimize the type and amount of weather resistance agent added to the film laminated on the decorative sheet (see, for example, Patent Documents 1 to 3, etc.).

[0003] Decorative sheets usually suffer from deterioration starting from the surface protective layer laminated on the outermost surface, and when the deteriorated surface protective layer shrinks, the extruded resin layer cannot keep up with the shrinkage of the surface protective layer, making the surface protective layer prone to peeling. That is, the weather resistance of the decorative sheet is improved simply by adding a weather resistant agent, but at the same time, it is necessary to suppress peeling between the surface protective layer and the layer located below it in order to further improve weather resistance. Furthermore, if the surface protective layer is too soft, the scratch resistance is reduced, whereas if it is too hard, the impact resistance is reduced. [Prior art documents] [Patent documents]

[0004] Patent Document 1: JP 2018-203866 A Patent Document 2: JP 2019-030998 A Patent Document 3: JP 2019-030999 A Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been made in view of the above-mentioned points, and aims to provide a film having excellent scratch resistance, impact resistance and weather resistance, and a decorative sheet having the film laminated on the outermost surface thereof, which also has excellent scratch resistance, impact resistance and weather resistance. [Means for solving the problem]

[0006] The inventors conducted extensive research into the weather resistance of a film having a structure in which a surface protective layer is laminated on a transparent resin layer, and as a result discovered that by controlling the difference in hardness between the surface protective layer and the transparent resin layer to be small, peeling between the surface protective layer and the transparent resin layer can be effectively prevented even if shrinkage of the surface protective layer occurs as deterioration progresses, and a film with excellent weather resistance can be obtained, thereby completing the present invention.

[0007] That is, the present invention is a film having at least a surface protective layer laminated on a transparent resin layer, wherein the difference in nanoindentation hardness between the surface protective layer and the transparent resin layer is 200 MPa or more and 270 MPa or less, the surface protective layer contains a thermosetting resin and / or an ionizing radiation curable resin, the transparent resin layer contains a homopolypropylene-based resin, the surface protective layer has a nanoindentation hardness of 300 MPa or more and 400 MPa or less, and the transparent resin layer has a nanoindentation hardness of 50 MPa or more and 140 MPa or less.

[0008] In the film of the present invention, the surface protective layer is preferably a mixture of a thermosetting resin and an ionizing radiation curable resin. Moreover, the surface protective layer preferably contains an isocyanate component, and the isocyanate component preferably contains at least one selected from the group consisting of hexamethylene diisocyanate, isophorone diisocyanate, and hydrogenated diphenylmethane diisocyanate (MDI). Moreover, the surface protective layer preferably contains a polyhydric alcohol, and the polyhydric alcohol preferably contains at least 2,2,4-trimethyl-1,3-pentanediol. Moreover, the surface protective layer preferably contains an acrylic polyol component, and the acrylic polyol component preferably contains at least one selected from the group consisting of methyl methacrylate (MMA), methacrylic acid, hydroxyethyl acrylate (HEA), and hydroxyethyl methacrylate (HEMA). Moreover, the surface protective layer preferably contains at least one agent selected from the group consisting of an antibacterial agent, an antiviral agent, and an antiallergen agent. The transparent resin layer preferably contains a spherical filler and / or an irregular filler. The transparent resin layer preferably contains at least one selected from the group consisting of magnesium, aluminum, and zinc. The present invention also relates to a decorative sheet having the above-mentioned film of the present invention laminated as the outermost layer. In addition, the decorative sheet of the present invention preferably contains a biomass-derived component. Effect of the Invention

[0009] The present invention can provide a film that has excellent scratch resistance, impact resistance, and weather resistance, and a decorative sheet that has excellent scratch resistance, impact resistance, and weather resistance by being provided with the film. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1A is a cross-sectional view that illustrates a schematic example of a film of the present invention, and FIG. 1B is a cross-sectional view that illustrates a schematic example of a film of the present invention according to another embodiment. [Diagram 2] 1(a) to 1(c) are diagrams illustrating a method for measuring nanoindentation hardness in this specification. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The film and decorative sheet of the present invention will now be described. In the following description, the lower and upper limits of a numerical range expressed with "to" means "greater than or equal to" (for example, if α~β, then it is greater than or equal to α and less than or equal to β).

[0012] <Film> FIG. 1(A) is a cross-sectional view that illustrates an example of the film of the present invention. As shown in Fig. 1, the film 1 of the present invention has at least a surface protective layer 2 laminated on a transparent resin layer 3. In the present invention, the surface protective layer 2 and the transparent resin layer 3 may be composed of a single layer as shown in Fig. 1(A), or may be composed of multiple layers, such as the surface protective layer 2' composed of the surface protective upper layer 2a and the surface protective lower layer 2b, and the transparent resin layer 3' composed of the transparent resin upper layer 3a and the transparent resin lower layer 3b, as shown in Fig. 1(B). In the present invention, the surface protective layer and the transparent resin layer may be composed of three or more layers.

[0013] In the film 1 of the present invention, the difference in nanoindentation hardness between the surface protective layer 2 and the transparent resin layer 3 is 200 MPa or more and 270 MPa or less. When the difference in nanoindentation hardness is 200 MPa or more and 270 MPa or less, it is possible to prevent insufficient weather resistance due to a decrease in adhesion between the surface protective layer 2 and the transparent resin layer 3 caused by shrinkage upon deterioration of the surface protective layer 2 due to the difference in scratch resistance and hardness between the surface protective layer 2 and the transparent resin layer 3. The preferred lower limit of the difference in nanoindentation hardness is 205 MPa, the preferred upper limit is 250 MPa, the more preferred lower limit is 210 MPa, and the more preferred upper limit is 230 MPa. In this specification, the "nanoindentation hardness" of each layer is the nanoindentation hardness measured using a surface film physical property tester Triboindenter (registered trademark) "TI-950" (manufactured by HYSITRON Corporation). The method for measuring the nanoindentation hardness (HIT) of each layer using a Triboindenter (registered trademark) "TI-950" is as follows.

[0014] (1) Using the Berkovich indenter shown in FIG. 2(a), the Berkovich indenter 21 is pressed into the measurement sample 20 in the direction of the arrow 22, which is the load direction, as shown in FIG. 2(b), under the indentation conditions described below. From the triangular pyramid-shaped geometric shape formed on the surface, the "contact projection area (Ap) (mm 2 The hardness is calculated by dividing the maximum test load (Fmax) by the Ap. That is, HIT=Fmax / Ap. (2) Here, the indentation conditions are as follows: at room temperature (laboratory environmental temperature), as shown in Figure 2(c), for the surface protection upper layer 2a, first a load of 0 to 100 μN is applied for 10 seconds (i.e., 10 μN / s), then a load of 100 μN (Fmax) is held for 5 seconds, and finally the load is removed from 100 to 0 μN for 10 seconds. Furthermore, for the transparent resin layer 3 described later, a load of 0 to 50 μN is first applied over 5 seconds (i.e., 10 μN / s), then a load of 50 μN (Fmax) is maintained for 5 seconds, and finally the load is removed from 50 to 0 μN over 10 seconds. Typically, the indentation amount (h) is about 100 to 150 nm, so the thickness of the layer to be measured as the sample in the indentation direction should be 1.0 μm or more (preferably 1.5 μm or more). Ap is 24.50 [hmax-ε(hmax-hr)] 2 (where ε is a correction factor due to the geometric shape of the indenter, and hr is the depth of the triangular pyramidal geometric shape remaining on the surface after unloading). (3) When measuring the hardness, the hardness of the cross section of the layer to be measured is measured to avoid the influence of the hardness of layers other than the layer to be measured, which is the measurement sample 20. That is, the film is embedded in resin (cold-curing type epoxy two-component curing resin) and left to harden at room temperature for 24 hours or more, and the hardened embedded sample is mechanically polished to expose the cross section of the layer to be measured, and the Berkovich indenter 21 is pressed into the cross section of the layer to be measured (at a position avoiding the fine particles if the layer contains fine particles such as filler) to measure the hardness of the cross section of each layer. In addition, the actual measurement is performed within a range from the outermost surface side of the cross section of each layer (the outermost surface side when made into a decorative sheet) to 1 / 3 of the cross section. In the case of the surface protective layer 2' consisting of the surface protective upper layer 2a and the surface protective lower layer 2b shown in Fig. 1(B), the nanoindentation hardness is measured within a range from the outermost surface side to 1 / 3 of the cross section of the surface protective layer 2' consisting of the surface protective upper layer 2a and the surface protective lower layer 2b combined, and in the case of the transparent resin layer 3' consisting of the transparent resin upper layer 3a and the transparent resin lower layer 3b, the nanoindentation hardness is measured within a range from the outermost surface side to 1 / 3 of the cross section of the transparent resin layer 3' consisting of the transparent resin upper layer 3a and the transparent resin lower layer 3b combined. (4) For each layer, the nanoindentation hardness is measured at 10 points to ensure that no bias occurs, and the average values ​​of the 10 points are regarded as the "nanoindentation hardness of the surface protective layer" and the "nanoindentation hardness of the transparent resin layer," respectively.

[0015] <Surface protective layer> In the present invention, the nanoindentation hardness of the surface protective layer 2 is 300 MPa or more and 400 MPa or less. If it is less than 300 MPa, the scratch resistance is poor, and if it exceeds 400 MPa, the impact resistance is poor. The nanoindentation hardness of the surface protective layer 2 is preferably 320 MPa in lower limit, 380 MPa in upper limit, 330 MPa in more preferable lower limit, and 370 MPa in more preferable upper limit.

[0016] In the present invention, the surface protective layer 2 contains a thermosetting resin and / or an ionizing radiation curable resin. Since the nanoindentation hardness of such a surface protective layer 2 can be set within the above-mentioned range, it can be adjusted according to the application. In addition, it is easy to add various additives as necessary. In particular, the surface protective layer 2 is preferably a mixture of a thermosetting resin and an ionizing radiation curable resin. When the surface protective layer 2 is a mixture of a thermosetting resin and an ionizing radiation curable resin, it is possible to further improve weather resistance in addition to scratch resistance.

[0017] In the present invention, the surface protective layer 2 preferably contains an isocyanate component. The isocyanate component is a component that functions as a curing agent for the thermosetting resin, and preferably contains at least one selected from the group consisting of hexamethylene diisocyanate, isophorone diisocyanate, and hydrogenated diphenylmethane diisocyanate (MDI). In the present invention, other isocyanate components may be contained. Examples of other isocyanate components include aromatic isocyanates such as 2,4-tolylene diisocyanate (TDI), xylylene diisocyanate (XDI), and naphthalene diisocyanate, as well as adducts or oligomers of these various isocyanates, such as an adduct of tolylene diisocyanate and a tolylene diisocyanate trimer.

[0018] In the present invention, the surface protective layer 2 preferably contains a polyhydric alcohol. The polyhydric alcohol is a component that functions as a base for the thermosetting resin, and it is preferable that the polyhydric alcohol contains at least 2,2,4-trimethyl-1,3-pentanediol. In the present invention, other polyhydric alcohols may be contained, for example, polyols such as polyethylene glycol, polypropylene glycol, butylene glycol, neopentyl glycol, and 1,6-hexanediol; and polyols having a hydroxyl group as a functional group, such as acrylic polyol, polyester polyol, polyether polyol, and urethane polyol.

[0019] In particular, the surface protective layer 2 preferably contains an acrylic polyol component. The acrylic polyol component preferably contains at least one selected from the group consisting of methyl methacrylate (MMA), methacrylic acid, hydroxyethyl acrylate (HEA), and hydroxyethyl methacrylate (HEMA), which increases the crosslink density of the thermosetting resin and improves scratch resistance. The acrylic polyol component is preferably contained in an amount of 50 parts by mass or more and 90 parts by mass or less relative to 100 parts by mass of the thermosetting resin.

[0020] In the surface protective layer 2 containing the polyhydric alcohol and the isocyanate component, the ratio of the polyhydric alcohol to the isocyanate component is not particularly limited, but for example, it is preferable that the isocyanate component is 5 to 30 parts by mass per 100 parts by mass of the polyhydric alcohol.

[0021] The ionizing radiation curable resin is a resin that is cured by irradiation with ionizing radiation, that is, electromagnetic waves or charged particle beams having an energy quantum capable of polymerizing or crosslinking molecules, such as ultraviolet rays (UV) or electron beams (EB), as well as electromagnetic waves such as X-rays and γ-rays, α-rays, charged particle beams such as ion beams, etc. Specifically, the ionizing radiation curable resin can be appropriately selected from commonly used polymerizable monomers, polymerizable oligomers, and prepolymers.

[0022] As the polymerizable monomer, for example, a (meth)acrylate monomer having a radical polymerizable unsaturated group in the molecule is suitable, and among them, a polyfunctional (meth)acrylate monomer is preferred. As the polyfunctional (meth)acrylate monomer, it is sufficient that it is a (meth)acrylate monomer having two or more ethylenically unsaturated bonds in the molecule, and for example, diethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, etc. are preferably mentioned. These (meth)acrylate monomers can be used alone or in combination of two or more kinds. In this specification, (meth)acrylate means acrylate or methacrylate.

[0023] Preferred examples of the polymerizable oligomer include oligomers having a radically polymerizable unsaturated group in the molecule, such as (meth)acrylate oligomers, such as urethane (meth)acrylate oligomers, epoxy (meth)acrylate oligomers, polyester (meth)acrylate oligomers, polyether (meth)acrylate oligomers, and acrylic (meth)acrylate oligomers. These polymerizable oligomers can be used alone or in combination of two or more kinds.

[0024] In addition, the decorative sheet of the present invention preferably contains a biomass-derived component. That is, in the present invention, either the isocyanate component or the acrylic polyol component may or may not contain a biomass-derived component. The biomass-derived component is not particularly limited, and examples thereof include biomass-derived polyethylene, biomass-derived polypropylene, and biomass-derived polybutylene.

[0025] The nanoindentation hardness of the surface protective layer 2 may be adjusted according to the desired value by appropriately changing, for example, the type of monomer or oligomer, the crosslinking density, the weight average molecular weight, mixing of different resins, and the like.

[0026] As the electron beam source, various electron beam accelerators such as Cockcroft-Wald type, Van de Graff type, resonant transformer type, insulating core transformer type, linear type, dynamitron type, high frequency type, etc. can be used. The energy of the electron beam is preferably about 100 to 1000 keV, more preferably about 100 to 300 keV. The dose of the electron beam is preferably about 2 to 15 Mrad.

[0027] The surface protective layer 2 may contain other additives. As the additives, ultraviolet absorbers, ultraviolet shielding agents, polymerization initiators, light stabilizers, abrasion resistance improvers, polymerization inhibitors, crosslinking agents, infrared absorbers, antistatic agents, adhesion improvers, leveling agents, thixotropy imparting agents, coupling agents, plasticizers, defoamers, fillers, antiblocking agents, dispersants, solvents, deodorants, antibacterial agents, antiviral agents, antiallergens, antifungal agents, and the like can be added within the scope of the object of the present invention.

[0028] Here, the dispersant is a dispersant having a hydroxyl group, an amino group, or an unsaturated double bond, and is preferably encapsulated in a vesicle having a monolayer outer membrane made of phospholipid. In other words, the surface protective layer 2 preferably contains a so-called "dispersant vesicle." The dispersion vesicles can be prepared, for example, by using the supercritical reverse phase evaporation method described below. In addition, the dispersant vesicle has a capsule outer membrane that is a monolayer membrane made of phospholipids, and the monolayer membrane encapsulates the dispersant. In the resin composition forming the surface protective layer 2, such a dispersant vesicle may exist in such a manner that the outer membrane made of phospholipids is broken, exposing the encapsulated dispersant and making contact with the resin composition.

[0029] The surface protective layer 2 may contain inorganic fine particles from the viewpoint of improving scratch resistance and adjusting nanoindentation hardness. Examples of the inorganic fine particles include silica, alumina, aluminosilicate, kaolinite, calcium carbonate, barium sulfate, and glass. Furthermore, by controlling the type and content of the inorganic fine particles, the nanoindentation hardness of the surface protective layer 2 can also be adjusted.

[0030] The average particle size of the inorganic fine particles is not critical, but is preferably 20 μm or less, more preferably 1 μm or more and 20 μm or less, and even more preferably 2 μm or more and 15 μm or less. The average particle size of the inorganic fine particles is the 50% particle size (d50: median size) when the particles in a solution are measured by a dynamic light scattering method and the particle size distribution is expressed as a cumulative volume distribution. The 50% particle size can be measured, for example, using a Microtrac particle size analyzer (manufactured by Nikkiso Co., Ltd.).

[0031] The content of the inorganic fine particles is preferably 1 part by mass or more and 30 parts by mass or less, more preferably 2 parts by mass or more and 25 parts by mass or less, and even more preferably 5 parts by mass or more and 20 parts by mass or less, relative to 100 parts by mass of the resin component forming the surface protective layer 2.

[0032] In the present invention, the inorganic fine particles contained in the surface protective layer 2 are preferably spherical and / or amorphous. By being spherical and / or amorphous, the filling density in the resin layer is increased and the dispersibility is further improved, which makes it easier to adjust to obtain the desired effect. Examples of the spherical inorganic fine particles include spherical silica, spherical alumina, and spherical calcium carbonate, with spherical silica being preferred among them. Examples of the amorphous inorganic fine particles include amorphous silica, alumina flakes, and amorphous magnesium carbonate, with amorphous silica being preferred among them. The transparent resin layer 3 described below also preferably contains the inorganic fine particles contained in the surface protective layer 2, and similarly to the above, the inorganic fine particles are more preferably spherical and / or amorphous.

[0033] In the present invention, the surface protective layer 2 preferably contains, as an ultraviolet absorbing agent, at least one selected from the group consisting of Tinuvin 329, Tinuvin 326, and Tinuvin P (all manufactured by BASF Japan Ltd.). The surface protective layer preferably contains at least Sanol LS765 (manufactured by Sankyo Co., Ltd.) as a light stabilizer. Furthermore, the surface protective layer 2 contains a component derived from a polyfunctional acrylate, and the component derived from a polyfunctional acrylate preferably contains at least one selected from the group consisting of pentaerythritol polyfunctional acrylate and dipentaerythritol polyfunctional acrylate.

[0034] In the present invention, the surface protective layer 2 preferably contains at least one agent selected from the group consisting of an antibacterial agent, an antiviral agent, and an antiallergen agent.

[0035] Antibacterial agents include inorganic antibacterial agents and organic antibacterial agents. In particular, inorganic antibacterial agents are preferable because they are generally safer than organic antibacterial agents and have excellent durability and heat resistance. Inorganic antibacterial agents include antibacterial metals such as silver, copper, zinc, etc. supported on various inorganic carriers.

[0036] When the surface protective layer 2 contains an antibacterial agent, the amount is preferably 0.1 to 10 parts by mass per 100 parts by mass of the heat-curable component or ionizing radiation-curable component, but can be appropriately adjusted depending on the type of antibacterial agent.

[0037] Antiviral agents can generally be broadly divided into organic and inorganic types. Examples of organic antiviral agents include quaternary ammonium salts, quaternary phosphonium salts, pyridines, pyrithiones, benzimidazoles, organic iodines, isothiazolinones, and anions. Inorganic antiviral agents include those in which metal ions such as silver, copper, and zinc are supported on zeolite, apatite, zirconia, glass, molybdenum oxide, and the like. When the surface protective layer contains an antiviral agent, the amount is preferably 0.1 to 10 parts by mass per 100 parts by mass of the heat-curable component or ionizing radiation-curable component, but can be appropriately adjusted depending on the type of antiviral agent.

[0038] As the anionic antiviral agent, for example, those containing a styrene polymer derivative compound and an unsaturated carboxylic acid derivative compound are preferable.

[0039] As the inorganic antiviral agent, a silver-based antiviral agent is preferable from the viewpoint of lack of biotoxicity and excellent safety, and among them, a phosphate glass-supported silver compound or a silver zeolite compound, and a molybdenum oxide-silver double salt compound are more preferable because they exhibit antiviral performance even in small amounts and therefore the amount added can be reduced.

[0040] The antiallergen agent contains either an inorganic compound or an organic compound, and each may be used alone or two or more different types may be mixed. The inorganic compound is preferably a material supporting a metal. The amount of the antiallergen agent added is preferably 1.0 to 40 parts by mass, more preferably 1 to 10 parts by mass, per 100 parts by mass of the heat-curable component or ionizing radiation-curable component, but can be appropriately adjusted depending on the type of antiallergen agent.

[0041] As the inorganic material of the inorganic compound, for example, at least one selected from the group consisting of titanium oxide, calcium phosphate, calcium silicate, zirconium phosphate, zeolite, silica alumina, magnesium silicate, and magnesium phosphate is preferable, and among these, titanium oxide, zirconium phosphate, etc. are more preferable.

[0042] The metal supported on the inorganic material is preferably at least one selected from the group consisting of gold, platinum, zinc and copper other than silver, and among these, zinc is preferred.

[0043] As a commercially available product, for example, "Atomy Ball TZ-R: Titanium oxide carrying zinc" manufactured by JGC Catalysts Co., Ltd. can be suitably used. These anti-allergen agents are effective against various allergens such as mites and pollen.

[0044] The organic compound is preferably a water-insoluble polymer containing a phenolic hydroxyl group, a polyphenol compound supported on an inorganic solid acid, or a polymer containing at least one monomer component selected from the group consisting of styrenesulfonic acid and its salts.

[0045] As the water-insoluble polymer containing a phenolic hydroxyl group, commercially available products such as "Allerbuster (trade name)" manufactured by Sekisui Chemical Co., Ltd. and "Marukalinker M (trade name)" manufactured by Maruzen Oil Co., Ltd. can be used. An example of a combination of the polyphenol compound and the zirconium compound is "Allerremove (trade name)" manufactured by Toa Gosei Co., Ltd. These anti-allergen agents are effective against various allergens such as mites and pollen.

[0046] The surface protective layer 2 can be formed by a known method using the above-mentioned materials. In the present invention, the thickness of the surface protective layer 2 is preferably 2 to 40 μm. If it is less than 2 μm, scratch resistance may be insufficient, and if it exceeds 40 μm, impact resistance and processability may be insufficient. The more preferred lower limit of the thickness of the surface protective layer 2 is 5 μm, and the more preferred upper limit is 30 μm. In the present invention, when the surface protective layer is composed of a plurality of layers, the total of the layers is preferably within the above-mentioned range. For example, in the surface protective layer 2' shown in Fig. 1(B), the total thickness of the surface protective upper layer 2a and the surface protective lower layer 2b is preferably within the above-mentioned range. The thickness of the surface protective upper layer 2a is preferably 1 to 30 µm, more preferably with a lower limit of 5 µm and a more preferred upper limit of 20 µm, and the thickness of the surface protective lower layer 2b is preferably 1 to 20 µm, more preferably with a lower limit of 5 µm and a more preferred upper limit of 10 µm.

[0047] <Transparent resin layer> In the present invention, the transparent resin layer 3 is not particularly limited as long as it allows the decorative sheet to be visible when laminated on a pattern layer of the decorative sheet, and includes any of colorless transparent, colored transparent, translucent, and the like. The transparent resin layer 3 has a nanoindentation hardness of 50 MPa or more and 140 MPa or less. If it is less than 50 MPa, the impact resistance may be insufficient, and if it exceeds 140 MPa, the processability may be insufficient. The transparent resin layer 3 has a nanoindentation hardness of preferably 55 MPa at its lower limit, 130 MPa at its upper limit, 80 MPa at its more preferable limit, and 125 MPa at its upper limit.

[0048] In the present invention, the transparent resin layer 3 contains a homopolypropylene resin. By containing a homopolypropylene resin, it is easy to adjust the nanoindentation range. As the homopolypropylene resin, for example, Novatec PP manufactured by Japan Polypropylene Corporation can be used. In particular, when it is intended to improve the surface strength of the film of the present invention, it is preferable to use a crystalline polypropylene resin as the homopolypropylene resin.

[0049] In this case, it is preferable that a nucleating agent encapsulated in a vesicle (nucleating agent vesicle) is added to the crystalline polypropylene resin. By adding a nucleating agent vesicle in which a nucleating agent is encapsulated to a vesicle having a single-layer outer membrane, a transparent resin layer 3 superior in transparency, scratch resistance, and post-processing resistance can be obtained. The nucleating agent vesicle can be prepared by the Bangham method, the extrusion method, the hydration method, the surfactant dialysis method, the reverse phase evaporation method, the freeze-thaw method, the supercritical reverse phase evaporation method, or the like.

[0050] Examples of the nucleating agent include metal phosphates, metal benzoates, metal pimelates, metal rosins, benzylidene sorbitol, quinacridone, cyanine blue, talc, etc. In particular, in order to maximize the effect of the nano-processing, it is preferable to use metal phosphates, metal benzoates, metal pimelates, and metal rosins, which are non-melting and can be expected to have good transparency, but when the material itself can be made transparent by the nano-processing, colored quinacridones, cyanine blue, talc, etc. can also be used. Furthermore, a non-melting type nucleating agent may be appropriately mixed with melting type benzylidene sorbitol.

[0051] In addition, various additives such as existing heat stabilizers, ultraviolet absorbers, light stabilizers, antiblocking agents, catalyst scavengers, colorants, light scattering agents, and gloss adjusters can also be added to the transparent resin layer 3 as necessary.

[0052] In the present invention, the transparent resin layer 3 may contain, for example, polyethylene, polypropylene other than the above homopolypropylene-based resins, olefin resins such as polybutene, polymethylpentene, and olefin-based thermoplastic elastomers, polyester resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, ethylene glycol-terephthalic acid-isophthalic acid copolymer resin, terephthalic acid-ethylene glycol-1,4-cyclohexanedimethanol copolymer resin, and polyester-based thermoplastic elastomers, acrylic resins such as polymethyl (meth)acrylate, methyl (meth)acrylate-butyl (meth)acrylate copolymer resin, and methyl (meth)acrylate-styrene copolymer resin, polycarbonate resin, polyvinyl chloride, polystyrene, and ionomers. Among these, polyethylene or polypropylene is more preferred because of its high tensile strength, excellent chemical resistance, and excellent production process.

[0053] The polyethylene may be a homopolymer of ethylene or a copolymer of ethylene and another comonomer copolymerizable with ethylene (e.g., an α-olefin such as propylene, 1-butene, 1-hexene, or 1-octene, vinyl acetate, or vinyl alcohol). Examples of polyethylene resins include high density polyethylene (HDPE), medium density polyethylene (MDPE), low density polyethylene (LDPE), linear low density polyethylene (LLDPE), very low density polyethylene (VLDPE), ultra high molecular weight polyethylene (UHMWPE), and cross-linked polyethylene (PEX). These polyethylenes may be used alone or in combination of two or more.

[0054] The polypropylene may be a copolymer of propylene and another comonomer copolymerizable with propylene (eg, α-olefins such as ethylene, 1-butene, 1-hexene, and 1-octene; vinyl acetate, vinyl alcohol, and the like). These polypropylenes may be used alone or in combination of two or more. From the viewpoint of bending processability, the polypropylene is preferably a random polypropylene (random PP).

[0055] The transparent resin layer 3 may be composed of one layer, such as the transparent resin layer 3 shown in FIG. 1(A), or may be composed of two layers, such as the transparent resin layer 3' shown in FIG. 1(B), or may be composed of three or more layers. When the transparent resin layer is composed of two or more layers, from the viewpoint of adhesion to the transparent adhesive layer described below, it is preferable that the side in contact with the transparent adhesive layer is a layer formed of maleic acid-modified polyethylene or maleic acid-modified polypropylene.

[0056] From the viewpoint of obtaining excellent scratch resistance and bending workability, the thickness of the transparent resin layer 3 is preferably 30 μm or more and 150 μm or less, and more preferably 40 μm or more and 120 μm or less.

[0057] In the present invention, when the transparent resin layer is composed of a plurality of layers, the total of the layers is preferably within the above-mentioned range. For example, in the transparent resin layer 3' shown in Fig. 1(B), the total thickness of the transparent resin upper layer 3a and the transparent resin lower layer 3b is preferably within the above-mentioned range. The thickness of the transparent resin upper layer 3a is preferably 15 to 75 µm, with a more preferred lower limit of 20 µm and a more preferred upper limit of 60 µm, and the thickness of the transparent resin lower layer 3b is preferably 15 to 75 µm, with a more preferred lower limit of 20 µm and a more preferred upper limit of 60 µm.

[0058] When the transparent resin layer is composed of a plurality of layers, the types of resins forming the layers may be the same or different, and the thicknesses may be the same or different. The method for laminating two or more transparent resin layers is not limited as long as it is a common method, and examples thereof include dry lamination and extrusion heat lamination.

[0059] When the transparent resin layer has a two-layer structure, each of the transparent resin layers may be laminated via a known adhesive layer, or may be laminated continuously by a thermal lamination method. As the above-mentioned thermal lamination method, a known method such as melt co-extrusion using a T-die can be used.

[0060] Moreover, the transparent resin layer 3 preferably contains at least one selected from the group consisting of magnesium, aluminum, and zinc. By containing these metal fillers, the fluidity of the resin is improved, the electrical conductivity is improved, and static electricity is less likely to accumulate, and non-flammability is improved. The amount of magnesium or the like added is preferably, for example, 0.01 parts by mass or more and 30 parts by mass or less per 100 parts by mass of the transparent resin, but is not limited to this as long as the desired effect is obtained.

[0061] The transparent resin layer 3 may be colored. In this case, a colorant may be added to the thermoplastic resin. As the colorant, the pigment or dye used in the design layer described below can be used.

[0062] The transparent resin layer 3 may be subjected to surface treatment such as saponification treatment, glow discharge treatment, corona discharge treatment, plasma treatment, ultraviolet (UV) treatment, and flame treatment, without departing from the spirit of the present invention.

[0063] The film of the present invention has a configuration in which a surface protective layer is laminated on at least a transparent resin layer, and the difference in hardness between the surface protective layer and the transparent resin layer is controlled to be small. Therefore, even if shrinkage of the surface protective layer occurs due to the progression of deterioration, peeling between the surface protective layer and the transparent resin layer can be suitably prevented, and the film can have excellent weather resistance.

[0064] A decorative sheet having the film of the present invention laminated on the outermost surface thereof also constitutes the present invention. The decorative sheet of the present invention may have a structure including, for example, a base sheet, a pattern layer, a transparent adhesive layer, and the film of the present invention in this order. The film of the present invention is laminated so that the transparent resin layer faces the transparent adhesive layer.

[0065] (Transparent adhesive layer) The transparent adhesive layer is not particularly limited, and any known adhesive may be used. Examples include polyurethanes, acrylics, polyolefins, polyvinyl acetates, polyvinyl chlorides, vinyl chloride-vinyl acetate copolymers, ethylene-acrylic acid copolymers, ionomers, as well as butadiene-acrylonitrile rubber, neoprene rubber, and natural rubber. These adhesives may be used alone or in combination of two or more.

[0066] The transparent adhesive layer preferably has a thickness after drying of about 0.1 to 30 μm, more preferably about 1 to 5 μm.

[0067] (Picture layer) The decorative sheet of the present invention may have a pattern layer from the viewpoint of improving the design.

[0068] The design layer may be, for example, a colored layer (so-called solid layer) that covers the entire surface, or a design layer formed by printing various patterns using ink and a printing machine, or a combination of these.

[0069] For example, when the background color of the substrate sheet described later is to be colored and concealed, the solid layer can improve the design while concealing the color. From the viewpoint of further improving the design, the solid layer and the pattern layer may be combined, while when the background pattern of the substrate sheet is to be utilized, only the pattern layer may be provided without using the solid layer.

[0070] The ink used for the design layer is a mixture of a binder, a pigment, a coloring material such as a dye, an extender pigment, a solvent, a stabilizer, a plasticizer, a catalyst, a hardener, an ultraviolet absorber, a light stabilizer, etc., as appropriate.

[0071] The binder is not particularly limited, and examples thereof include urethane resin, acrylic polyol resin, acrylic resin, ester resin, amide resin, butyral resin, styrene resin, urethane-acrylic copolymer, polycarbonate-based urethane-acrylic copolymer (urethane-acrylic copolymer derived from a polymer (polycarbonate polyol) having a carbonate bond in the polymer main chain and having two or more hydroxyl groups at the end and side chain), vinyl chloride-vinyl acetate copolymer resin, vinyl chloride-vinyl acetate-acrylic copolymer resin, chlorinated propylene resin, nitrocellulose resin, cellulose acetate resin, etc. These binders can be used alone or in combination of two or more kinds.

[0072] As the coloring material, from the viewpoint of coloring and concealing the ground color of the substrate described below and improving the design, for example, inorganic pigments such as white pigments, iron black, yellow lead, titanium yellow, red iron oxide, cadmium red, ultramarine blue, cobalt blue, etc.; organic pigments or dyes such as quinacridone red, isoindolinone yellow, phthalocyanine blue, etc.; metal pigments consisting of scaly foil flakes of aluminum, brass, etc.; and pearlescent pigments consisting of scaly foil flakes of titanium dioxide-coated mica, basic lead carbonate, etc. can be used.

[0073] When the design layer is present, the pattern may be a wood grain pattern, a marble pattern (e.g., travertine marble pattern) or other stone pattern imitating the surface of rock, a fabric pattern imitating a cloth or fabric-like pattern, a tiled pattern, a brickwork pattern, or a combination of these, such as marquetry or patchwork. These patterns can be formed by multi-color printing using the usual process colors of yellow, red, blue, and black, or by multi-color printing using special colors, which is performed by preparing plates of the individual colors that make up the pattern.

[0074] The thickness of the pattern layer may be appropriately selected depending on the desired pattern, but from the viewpoint of coloring and concealing the background color of the base sheet and improving the design, it is preferably 0.5 to 20 μm, more preferably 1 to 10 μm, and even more preferably 2 to 5 μm.

[0075] (Base sheet) The substrate sheet is preferably a layer made of an olefin resin or a polyester resin. As the olefin resin forming the above-mentioned base sheet, the same olefin resins capable of forming the transparent resin layer 3 can be exemplified. Among these, polyethylene and polypropylene are preferred from the viewpoint of excellent scratch resistance and bending processability. The resin forming the base sheet may be a polyester resin, and preferred examples of the polyester resin include polyethylene terephthalate, polynaphthalene terephthalate, polybutylene terephthalate, and PET-G. From the viewpoint of excellent scratch resistance and bending processability, polybutylene terephthalate and PET-G are more preferred.

[0076] The base sheet may be colored as necessary. In this case, a coloring material may be added to the olefin resin or the like. As the coloring material, the pigments or dyes used in the design layer described above can be used.

[0077] From the viewpoint of excellent scratch resistance and bending processability, the thickness of the above-mentioned base sheet is preferably 30 μm or more and 120 μm or less, more preferably 40 μm or more and 110 μm or less, even more preferably 50 μm or more and 100 μm or less, and particularly preferably 55 μm or more and 95 μm or less.

[0078] (others) The decorative sheet of the present invention may have a primer layer, a backer layer, and the like, if necessary.

[0079] The primer layer can be formed by applying a known primer agent. Examples of the primer agent include a urethane resin-based primer agent made of an acrylic modified urethane resin (acrylic urethane resin), a primer agent made of a urethane-cellulose resin (for example, a resin obtained by adding hexamethylene diisocyanate to a mixture of urethane and soluble nitrocellulose), and a resin-based primer agent made of a block copolymer of acrylic and urethane. The primer agent may contain additives as necessary. Examples of additives include fillers such as calcium carbonate and clay, flame retardants such as magnesium hydroxide, antioxidants, lubricants, foaming agents, ultraviolet absorbers, and light stabilizers. The amount of additives to be added can be appropriately set depending on the product characteristics.

[0080] The primer layer may contain an ultraviolet absorbing agent, if necessary. As the ultraviolet absorbing agent, any known ultraviolet absorbing agent can be appropriately selected and used.

[0081] The primer layer can be provided, for example, on one or both sides of the transparent resin layer 3, on one or both sides of the base sheet, or the like.

[0082] The thickness of the primer layer is not particularly limited, but is, for example, preferably 0.01 to 10 μm, and more preferably 0.1 to 1 μm.

[0083] The decorative sheet of the present invention may have a backer layer as the bottom layer (the side opposite to the side on which the design layer is laminated) of the base sheet, from the viewpoint of imparting scratch resistance and impact resistance. As the backer layer, a known backer layer disclosed in, for example, JP-A-2014-188941 can be appropriately selected and used. The thickness of the backer layer is preferably, for example, 50 μm to 500 μm.

[0084] (Uneven shape) The decorative sheet of the present invention may be provided with a concave-convex shape by heat embossing. The above uneven shape needs to be present at least in the surface protective layer 2 of the decorative sheet of the present invention, and the depth of the uneven shape may be limited to within the surface protective layer 2 or may extend to the transparent resin layer 3.

[0085] Examples of the uneven pattern include a duct groove of a wood grain board, an uneven surface of a stone board, a cloth surface texture, a matte finish, a sand grain, a hairline, a striped groove, etc. From the viewpoint of improving the design, it is preferable that the uneven pattern is a pattern that is in harmony with the pattern of the design layer. For example, if the design layer has a wood grain pattern, a wood grain duct groove can be selected as the pattern of the recesses, and the wood grain of the design layer and the wood grain of the recesses can be made to match, resulting in a decorative sheet that is more realistic, full of texture, and has a luxurious feel.

[0086] (Method of manufacturing decorative sheets) An example of a manufacturing method for the decorative sheet of the present invention will be described using as an example a decorative sheet having the film of the present invention consisting of a base sheet, a pattern layer, a transparent adhesive layer, a transparent resin layer, and a surface protective layer in this order.

[0087] First, a resin composition for forming the above-mentioned base sheet is prepared, and the base sheet is formed into a film by a method such as melt extrusion, and a design layer is formed on the base sheet. Separately, a resin composition for forming the transparent resin layer 3 is prepared, and the transparent resin layer 3 is formed by a method such as melt extrusion, and the pattern layer and the transparent resin layer 3 are bonded together via a transparent adhesive layer. Thereafter, a raw material composition for the surface protective layer 2 is applied onto the transparent resin layer 3 to form a coating film, which is then cured by irradiating it with ionizing radiation and / or by heating, to form the surface protective layer 2.

[0088] When the decorative sheet of the present invention is to be provided with a concave-convex shape, it may be provided by, for example, embossing. The embossing may be carried out, for example, by a method in which embossing is carried out from the side of the decorative sheet of the present invention having the surface protective layer 2 using a well-known sheet-type or rotary embossing machine.

[0089] The present specification discloses the following:

[0090] The present disclosure (1) is a film including at least a transparent resin layer and a surface protective layer laminated thereon, the difference in nanoindentation hardness between the surface protective layer and the transparent resin layer being 200 MPa or more and 270 MPa or less, and the surface protective layer containing a thermosetting resin and / or an ionizing radiation curable resin, The transparent resin layer is a film containing a homopolypropylene resin, the surface protective layer having a nanoindentation hardness of 300 MPa or more and 400 MPa or less, and the transparent resin layer having a nanoindentation hardness of 50 MPa or more and 140 MPa or less. The present disclosure (2) is the film according to the present disclosure (1), wherein the surface protective layer is a mixture of a thermosetting resin and an ionizing radiation curable resin. The present disclosure (3) is the film according to the present disclosure (1) or (2), wherein the surface protective layer contains an isocyanate component, and the isocyanate component contains at least one selected from the group consisting of hexamethylene diisocyanate, isophorone diisocyanate, and hydrogenated diphenylmethane diisocyanate (MDI). The present disclosure (4) is the film according to any one of the present disclosures (1) to (3), in which the surface protective layer contains a polyhydric alcohol, and the polyhydric alcohol contains at least 2,2,4-trimethyl-1,3-pentanediol. The present disclosure (5) is the film according to any one of the present disclosures (1) to (4), wherein the surface protective layer contains an acrylic polyol component, and the acrylic polyol component includes at least one selected from the group consisting of methyl methacrylate (MMA), methacrylic acid, hydroxyethyl acrylate (HEA), and hydroxyethyl methacrylate (HEMA). The present disclosure (6) is the film according to any one of the present disclosures (1) to (5), wherein the surface protective layer contains at least one agent selected from the group consisting of an antibacterial agent, an antiviral agent, and an antiallergen agent. The present disclosure (7) is the film according to any one of the present disclosures (1) to (6), in which the transparent resin layer contains a spherical filler and / or an irregular filler. The present disclosure (8) is the film according to any one of the present disclosures (1) to (7), in which the transparent resin layer contains at least one selected from the group consisting of magnesium, aluminum, and zinc. The present disclosure (9) is a decorative sheet having the film according to any one of the present disclosures (1) to (8) laminated as the outermost layer. The present disclosure (10) is a decorative sheet according to the present disclosure (9), which contains a biomass-derived component. EXAMPLES

[0091] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples.

[0092] As the transparent resin layer used in the examples and comparative examples, a highly crystalline homopropylene resin or a transparent resin layer to which a nucleating agent vesicle was added was used. A method for producing a transparent resin layer containing nucleating agent vesicles will be described below.

[0093] <Preparation of nucleating agent vesicles> Nucleating agent vesicles are prepared by supercritical reverse phase evaporation, by first placing 100 parts by weight of methanol, 82 parts by weight of a phosphate metal salt nucleating agent (ADEKA STAB NA-11, manufactured by ADEKA Corporation) as the nucleating agent, and 5 parts by weight of phosphatidylcholine as the substance that constitutes the outer membrane of the vesicle in a high-pressure stainless steel container maintained at 60°C and sealing it, injecting carbon dioxide so that the pressure becomes 20 MPa to bring the mixture into a supercritical state, and then injecting 100 parts by weight of ion-exchanged water while vigorously stirring and mixing. After stirring for 15 minutes while maintaining the temperature and pressure inside the container at a supercritical state, carbon dioxide was discharged and the pressure was returned to atmospheric pressure, thereby preparing nucleating agent vesicles with a single-layer outer membrane made of phospholipids.

[0094] <Method for producing transparent resin layer containing nucleating agent vesicles> The resin composition forming the transparent resin layer is a highly crystalline homopropylene resin having a pentad fraction of 97.8%, an MFR (melt flow rate) of 15 g / 10 min (230°C), and a molecular weight distribution MWD (Mw / Mn) of 2.3, to which 500 ppm of a hindered phenol-based antioxidant (Irganox 1010, manufactured by BASF) has been added, 2000 ppm of a benzotriazole-based ultraviolet absorber (Tinuvin 328, manufactured by BASF), 2000 ppm of a hindered amine light stabilizer (Chimasorb 944, manufactured by BASF), and 1000 ppm of the above-mentioned nucleating agent vesicle. The resin composition was then melt-extruded using a melt extruder to form a transparent resin layer.

[0095] Example 1 A resin containing 100 parts by mass of highly crystalline homopolypropylene resin (Novatec PP, product name FY4, manufactured by Mitsubishi Chemical Corporation), 0.5 parts by mass of a hindered phenol-based antioxidant (Irganox 1010; manufactured by BASF), 0.5 parts by mass of a triazine-based ultraviolet absorber (CYASORBUV-1164; manufactured by SUNCHEM), and 0.5 parts by mass of a NOR-type light stabilizer (Tinuvin 622SF; manufactured by BASF) was melt-extruded using an extruder to form a sheet-shaped transparent resin layer made of a transparent highly crystalline polypropylene sheet having a thickness of 60 μm. The nanoindentation hardness was adjusted to the hardness shown in Table 1 by controlling the temperature during extrusion. Corona treatment was performed on both sides of the obtained transparent resin layer.

[0096] A pattern of unevenness was applied to the surface of this transparent resin layer by hot-press embossing, and the composition for forming the surface protective layer described below was used to sequentially apply a composition containing a thermosetting resin (hereinafter referred to as the thermosetting composition; coating amount after drying (described as film thickness after drying; same below): 5 μm) and a photocurable composition (coating amount after drying: 10 μm) to form a surface protective layer consisting of two layers, a thermocurable layer (lower surface protective layer) and a photocurable layer (upper surface protective layer), thereby obtaining the film of Example 1 having the nanoindentation hardness shown in Table 1.

[0097] (Composition for forming surface protective layer) <Thermosetting composition> Polyol solution A: 80 parts by weight In a four-neck flask equipped with a stirrer, a nitrogen inlet tube, and a reflux condenser, 80 g of methyl methacrylate and 20 g of 2-hydroxyethyl methacrylate were introduced, 100 g of ethyl acetate was added to dissolve, and the mixture was stirred in a nitrogen atmosphere on an oil bath. Polymerization was initiated by adding 0.2 g of α,α'-azobisisobutyronitrile, and the mixture was heated and stirred for 5 hours on a 60°C oil bath to obtain a colorless, viscous polyol solution A. Hardener: 5.0 parts by weight Product name: Hydrogenated MDI (hydrogenated diphenylmethane diisocyanate, manufactured by Evonik) UV absorber: 5.0 parts by weight Product name: Tinuvin 326 (manufactured by BASF) Light stabilizer: 2.0 parts by weight Product name: Sanol LS765 (manufactured by BASF) ·Dilution solvent: 50 parts by mass Product name: Ethyl acetate <Photocurable composition> ·UV resin: 90 parts by mass Product name: UA-33H (manufactured by Shin-Nakamura Chemical Industry Co., Ltd.) Properties: Molecular weight 1400, number of functional groups 9 Photoinitiator: 8 parts by weight Product name: Irgacure 184 (manufactured by BASF) Light stabilizer: 2.0 parts by weight Product name: Sanol LS765 (manufactured by BASF) ·Dilution solvent: 60 parts by mass Product name: Ethyl acetate

[0098] Example 2 Manufacturing method of decorative sheet A pattern layer was provided on one side of a 60 μm thick base sheet having hiding power, and a primer coat was applied to the other side of the base sheet. Thereafter, the transparent resin layer obtained in Example 1 was attached to the surface of the design layer of the substrate sheet with an adhesive, and a concave-convex pattern was applied from the transparent resin layer side by hot-press embossing. In addition, a decorative sheet of Example 2 having a film formed by forming a surface protective layer was obtained in the same manner as in Example 1, except that the ultraviolet absorber to be blended into the thermosetting composition for forming the surface protective layer was changed to Tinuvin 399 (manufactured by BASF).

[0099] Example 3 A transparent resin layer was formed in the same manner as in Example 1, except that 10 parts by mass of an olefin-based elastomer resin (Prime TPO J5900, manufactured by Prime Polymer Co., Ltd.) was mixed with 100 parts by mass of a highly crystalline homopolypropylene resin (Novatec PP, product name FY4, manufactured by Mitsubishi Chemical Corporation) and the nanoindentation hardness was adjusted to the hardness shown in Table 1. Next, a pattern layer was provided on one side of a 60 μm thick base sheet having hiding properties, and a primer coat was applied to the other side of the base sheet. Thereafter, the obtained transparent resin layer was attached to the surface of the design layer of the substrate sheet with an adhesive, and a concave-convex pattern was applied from the transparent resin layer side by hot-press embossing. For the surface protection layer, 2.5 parts by mass each of Tinuvin 326 and Tinuvin 399 were blended as ultraviolet absorbers in the thermosetting composition for forming the surface protection layer, and the UV resin of the photocurable layer composition was changed to a hexafunctional aliphatic urethane acrylate oligomer (UA306H, manufactured by Kyoeisha Chemical Co., Ltd.). Except for this, the surface protection layer was formed in the same manner as in Example 1, and the decorative sheet of Example 3 was obtained.

[0100] Example 4 A transparent resin layer containing nucleating agent vesicles was formed to the thickness shown in Table 1. Next, a pattern layer was provided on one side of a 60 μm thick base sheet having hiding properties, and a primer coat was applied to the other side of the base sheet. Thereafter, a transparent resin layer containing nucleating agent vesicles was attached to the surface of the design layer of the base sheet with an adhesive, and a concave-convex pattern was applied from the transparent resin layer side by hot-press embossing. For the surface protection layer, the composition for forming the surface protection layer described below was used to coat the surface protection layer (coating amount 15 μm after drying), and the layer was semi-cured by heating at 60°C for 5 minutes. The layer was then irradiated with ultraviolet light having a wavelength of 300 nm using an ultraviolet irradiation device to obtain a decorative sheet of Example 4 having a film with the nanoindentation hardness shown in Table 1.

[0101] (Composition for forming surface protective layer) <Thermosetting resin> Two-component curing urethane top coat: 60 parts by weight Product name: W184 (DIC Graphics) Hardener: 5.0 parts by weight Product name: Duranate TPA-100 (manufactured by Asahi Kasei Corporation) UV absorbers: 2.5 parts by weight each Product name: Tinuvin 326 (manufactured by BASF), Tinuvin 399 (manufactured by BASF) Light stabilizer: 2.0 parts by weight Product name: Sanol LS765 (manufactured by BASF) <Light curing resin> Photocurable urethane acrylate: 40 parts by weight Product name: Unidic 17-824-9 (manufactured by DIC Graphics) Photoinitiator: 8 parts by weight Product name: Irgacure 184 (manufactured by BASF) Light stabilizer: 2.0 parts by weight Product name: Sanol LS765 (manufactured by BASF) Dispersant: 0.05 parts by weight Product name: KBM-503 (3-methacryloxypropyltrimethoxysilane) (manufactured by Shin-Etsu Chemical Co., Ltd.) ·Dilution solvent: 60 parts by mass Product name: Ethyl acetate

[0102] Example 5 A film was obtained in the same manner as in Example 1, except that the following antiallergen agent was added to the photocurable composition used as the surface protective layer. Antiallergen: 5 parts by weight Product name: Areli Move (manufactured by Toagosei)

[0103] Comparative Example 1 A transparent resin layer containing nucleating agent vesicles was formed to the thickness shown in Table 1. Next, a pattern layer was provided on one side of a 60 μm thick base sheet having hiding properties, and a primer coat was applied to the other side of the base sheet. Thereafter, a transparent resin layer containing nucleating agent vesicles was attached to the surface of the design layer of the base sheet with an adhesive, and a concave-convex pattern was applied from the transparent resin layer side by hot-press embossing. For the surface protective layer, the composition for forming the surface protective layer described below was used, and a surface protective layer (coating amount 15 μm after drying) was applied to obtain a decorative sheet of Comparative Example 1 having a film having the nanoindentation hardness shown in Table 1. <Surface protective layer forming composition> - 60 parts by weight of a two-component curing urethane top coat (W184, manufactured by DIC Graphics), a thermosetting resin 40 parts by weight of photocurable urethane acrylate (Unidic 17-824-9, manufactured by DIC Graphics), a photocurable resin 0.05 parts by weight of dispersant vesicles prepared using 3-methacryloxypropyltrimethoxysilane (KBM-503, Shin-Etsu Chemical Co., Ltd.) as a dispersant having an unsaturated double bond Inorganic nanoparticles: 0.05 parts by weight of silica nanoparticles with a particle size of 40 nm (AEROSIL OX50, manufactured by Eponic Co., Ltd.) <Preparation of Dispersant Vesicles> Dispersant vesicles were prepared by supercritical reverse phase evaporation, by first placing 100 parts by weight of methanol, 70 parts by weight of alcohol-modified silicone oil (XF42-B0970, Momentive Performance Materials) as a dispersant having hydroxyl groups, and 5 parts by weight of phosphatidylcholine as the phospholipid that constitutes the outer membrane of the vesicle in a high-pressure stainless steel container maintained at 60°C and sealing it, and then injecting carbon dioxide into the container until the pressure reached 20 MPa, creating a supercritical state. Thereafter, the contents of the container are vigorously stirred and 100 parts by weight of ion-exchanged water is poured into the container. After stirring and mixing for an additional 15 minutes while maintaining the temperature and pressure in a supercritical state, carbon dioxide was released from the container and the pressure was returned to atmospheric pressure, yielding dispersant vesicles containing a hydroxyl-containing dispersant inside a vesicle with a monolayer outer membrane made of phospholipids. Furthermore, by changing the above dispersant to 3-aminopropyltrimethoxysilane (KBM-903, Shin-Etsu Chemical Co., Ltd.) as a dispersant having an amino group, or 3-methacryloxypropyltrimethoxysilane (KBM-503, Shin-Etsu Chemical Co., Ltd.) as a dispersant having an unsaturated double bond, it is possible to obtain dispersant vesicles containing dispersants having each reactive group.

[0104] The films obtained in the examples and comparative examples were evaluated as follows.

[0105] (Nanoindentation hardness measurement method) The method for measuring the nanoindentation hardness (HIT) of each layer of the film according to the examples and comparative examples using a Triboindenter (registered trademark) "TI-950" is as follows. (1) Using the Berkovich indenter shown in FIG. 2(a), the Berkovich indenter 21 is pressed into the measurement sample 20 in the direction of the arrow 22, which is the load direction, as shown in FIG. 2(b), under the indentation conditions described below. From the triangular pyramid-shaped geometric shape formed on the surface, the "contact projection area (Ap) (mm 2 The hardness is calculated by dividing the maximum test load (Fmax) by the Ap. That is, HIT=Fmax / Ap. (2) Here, the indentation conditions are as follows: at room temperature (laboratory environmental temperature), as shown in Figure 2(c), for the surface protection layer 2, first a load of 0 to 100 μN is applied for 10 seconds (i.e., 10 μN / s), then a load of 100 μN (Fmax) is held for 5 seconds, and finally the load is removed from 100 to 0 μN for 10 seconds. Moreover, the transparent resin layer 3 is first subjected to a load of 0 to 50 μN for 5 seconds (i.e., 10 μN / s), then held at a load of 50 μN (Fmax) for 5 seconds, and finally unloaded from 50 to 0 μN for 10 seconds. Typically, the indentation amount (h) is about 100 to 150 nm, so the thickness of the layer to be measured as the sample in the indentation direction should be 1.0 μm or more (preferably 1.5 μm or more). Ap is 24.50 [hmax-ε(hmax-hr)] 2 (where ε is a correction factor due to the geometric shape of the indenter, and hr is the depth of the triangular pyramidal geometric shape remaining on the surface after unloading). (3) When measuring the hardness, the hardness of the cross section of the layer to be measured is measured to avoid the influence of the hardness of layers other than the layer to be measured, which is the measurement sample 20. That is, the film is embedded in resin (cold-curing type epoxy two-component curing resin) and left to harden at room temperature for 24 hours or more, and the hardened embedded sample is mechanically polished to expose the cross section of the layer to be measured, and the Berkovich indenter 21 is pressed into the cross section of the layer to be measured (at a position avoiding the fine particles if the layer contains fine particles such as filler) to measure the hardness of the cross section of each layer. In addition, the actual measurement is performed in the range from the outermost layer side (the outermost side when made into a decorative sheet) to 1 / 3 of the cross section of each layer. In the case of the surface protective layer 2' consisting of the surface protective upper layer 2a and the surface protective lower layer 2b shown in Fig. 1(B), the nanoindentation hardness is measured in the range from the outermost layer side to 1 / 3 of the cross section of the surface protective layer 2' consisting of the combined surface protective upper layer 2a and surface protective lower layer 2b. (4) For each layer, the nanoindentation hardness is measured at 10 points to ensure that no bias occurs, and the average values ​​of the 10 points are regarded as the "nanoindentation hardness of the surface protective layer" and the "nanoindentation hardness of the transparent resin layer," respectively.

[0106] (Scratch resistance (coin scratch)) The decorative sheets produced in the Examples and Comparative Examples were bonded to a 2.5 mm thick medium density fiberboard (MDF; decorative board substrate) using a water-soluble emulsion adhesive to produce a decorative board. For Example 1, the resulting film was bonded to a 2.5 mm thick medium density fiberboard (MDF; decorative board substrate) using a water-soluble emulsion adhesive to produce a laminate. The water-soluble emulsion adhesive used was as follows: Water-soluble emulsion adhesive Base: "BA-10L" manufactured by Japan Coating Resin Co., Ltd. Modified ethylene vinyl acetate Hardener: "BA-11B" manufactured by Japan Coating Resin Co., Ltd. Isocyanate-based Mixture ratio Base: Hardener = 100:2.5 (mass ratio) The decorative plate (laminate) was used to evaluate the scratch resistance by a coin scratch test. Specifically, two 10-yen coins tilted at 45° were placed in contact with the test surface (surface protection layer side) and dragged horizontally while applying a load (7 kg load), and the scratch state was evaluated. The results are shown in Table 1. The evaluation criteria are as follows: <Judgment criteria> +: No scratches found under 7kg load -: Scratches are observed under 7kg load

[0107] (Impact resistance (DuPont)) The impact resistance of the decorative boards (laminates) produced in the examples and comparative examples was evaluated using a DuPont impact tester (compliant with JIS K5600-5-3). Specifically, a weight of a specified weight was dropped from a height of 300 mm onto the surface of the decorative board (laminate) to evaluate whether or not cracks occurred in the decorative sheet (film). The results are shown in Table 1. The evaluation criteria are as follows: +: If you look carefully, you can see tiny cracks. -: Cracks are clearly visible

[0108] (weather resistance) The decorative sheets (films for Example 1) produced in the Examples and Comparative Examples were subjected to the following accelerated weathering test using a black panel temperature of 63°C and an illuminance of 100mW / cm 2 The cycle of irradiating the sheet with ultraviolet light for 20 hours under the above conditions and then condensing for 4 hours was repeated. After 300 hours had passed, the appearance of the decorative sheet was visually evaluated. The results are shown in Table 1. <Ultra-accelerated weather resistance test equipment> Ultra-accelerated weather resistance test equipment (product name: "Eye Super UV Tester SUV-W161", manufactured by Iwasaki Electric Co., Ltd.) equipped with a UV lamp (product name: M04-L21WB / SUV, manufactured by Iwasaki Electric Co., Ltd.), a lamp jacket (product name: WJ50-SUV, manufactured by Iwasaki Electric Co., Ltd.), and an illuminometer (product name: UVD-365PD, manufactured by Iwasaki Electric Co., Ltd.) <Evaluation criteria> +: No cracks -: Cracks have occurred

[0109] (Anti-allergen performance) The films prepared in Examples 1 and 5 were evaluated for anti-allergen performance as follows. The inactivation rate of mite allergen was measured using an ITEA mite allergen (Der f 1) ELISA kit (manufactured by ITEA). A mite allergen solution was prepared by adjusting the initial concentration of the allergen standard solution included in the kit to 100 ng / mL using a dilution solution. 5cm of film 2 The test specimen was cut into pieces, and 400 μL of the mite allergen solution was dropped onto the specimen, measuring 5 cm. 2 After covering each test specimen with a PE film and leaving it for 24 hours, the mite allergen on each test specimen was collected and the inactivation rate of the mite allergen was measured using the ELISA method, and the anti-allergen performance was evaluated according to the following criteria. Allergen inactivation rate = (1-amount of remaining allergen / initial amount of allergen) x 100 (%) <Formula 1> The allergen inactivation rate was evaluated by measuring the absorbance of the initial allergen amount and the amount of allergen after collection, and then using the above formula 1. The results are shown in Table 2. <Criteria for determining anti-allergen performance> +: Inactivation rate of mite allergens from their initial activity level is 70% or more -: Inactivation rate of mite allergens from their initial activity level is less than 70%

[0110] [Table 1]

[0111] [Table 2]

[0112] As shown in Table 1, the film of the embodiment had a difference in nanoindentation hardness between the surface protective layer and the transparent resin layer of 200 MPa or more and 270 MPa or less, a nanoindentation hardness of the surface protective layer of 300 MPa or more and 400 MPa or less, and a nanoindentation hardness of the transparent resin layer of 50 MPa or more and 140 MPa or less, and all evaluation results for scratch resistance, impact resistance, and weather resistance were good. On the other hand, the film of Comparative Example 1 had a large difference in nanoindentation hardness between the surface protection layer and the transparent resin layer, at 302 MPa, and the nanoindentation hardness of the surface protection layer, at 419.6 MPa, so that it had excellent scratch resistance but poor impact resistance and weather resistance. Furthermore, as can be seen from Table 2, the surface protective layer can impart anti-allergen performance by including an anti-allergen agent. [Explanation of symbols]

[0113] 1,1' Film 2, 2' surface protective layer 2a Surface protection upper layer 2b Surface protection lower layer 3, 3' transparent resin layer 3a Transparent resin upper layer 3b Transparent resin lower layer 20 Measurement data 21 Berkovich indenter 22 Load direction

Claims

1. A film having a surface protective layer laminated on at least a transparent resin layer, a difference in nanoindentation hardness between the surface protective layer and the transparent resin layer is 200 MPa or more and 270 MPa or less; the surface protective layer contains a thermosetting resin and / or an ionizing radiation curable resin, The transparent resin layer contains a homopolypropylene resin, The nanoindentation hardness of the surface protective layer is 300 MPa or more and 400 MPa or less, The transparent resin layer has a nanoindentation hardness of 50 MPa or more and 140 MPa or less.

2. The film according to claim 1 , wherein the surface protective layer is a mixture of a thermosetting resin and an ionizing radiation curable resin.

3. The surface protective layer contains an isocyanate component, The film according to claim 1 or 2, wherein the isocyanate component comprises at least one selected from the group consisting of hexamethylene diisocyanate, isophorone diisocyanate, and hydrogenated diphenylmethane diisocyanate (MDI).

4. The surface protective layer contains a polyhydric alcohol, The film according to claim 1 or 2, wherein the polyhydric alcohol comprises at least 2,2,4-trimethyl-1,3-pentanediol.

5. The surface protective layer contains an acrylic polyol component, 3. The film of claim 1 or 2, wherein the acrylic polyol component comprises at least one member selected from the group consisting of methyl methacrylate (MMA), methacrylic acid, hydroxyethyl acrylate (HEA), and hydroxyethyl methacrylate (HEMA).

6. The film according to claim 1 or 2, wherein the surface protective layer comprises at least one selected from the group consisting of an antibacterial agent, an antiviral agent, and an antiallergen agent.

7. The film according to claim 1 or 2, wherein the transparent resin layer contains a spherical filler and / or an irregular filler.

8. The film according to claim 1 or 2, wherein the transparent resin layer contains at least one selected from the group consisting of magnesium, aluminum, and zinc.

9. A decorative sheet having the film according to claim 1 or 2 laminated as the outermost layer.

10. The decorative sheet according to claim 9 , comprising a biomass-derived component.